SUBSTANTIVE ENVIRONMENTAL LAW COMPLIANCE OF OIL PALM LICENSING AND STATE RESPONSIBILITY FOR FLOODS IN SUMATRA - Adhika Mahindra Satya; Kenneth; Syahban Alvian Hamonangan Harianja; Rivaldo William Krisma Waruwu (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
Large-scale oil palm plantation development has transformed Sumatra into a strategic economic region while intensifying environmental degradation and recurrent flooding associated with forest conversion. These conditions raise legal questions regarding the substantive compliance of plantation licensing policies with environmental law principles and the scope of state responsibility for ecological disasters. This study examines whether oil palm plantation licensing in Sumatra substantially complies with environmental law and whether recurrent floods justify classification as a national disaster with implications for state responsibility. Using a normative legal research method, this study applies statutory, conceptual, and case-based approaches grounded in constitutional, environmental, forestry, plantation, and disaster management laws. The findings show that although plantation licensing policies largely comply with formal administrative requirements, the government fails to satisfy substantive environmental law principles, including the precautionary principle, prevention, sustainable development, and the polluter-pays principle. Licenses authorising forest conversion have contributed to structural environmental degradation and increased flood risks. Under the prevailing fault-based legal framework, state liability for flood disasters resulting from licensing policies remains limited, despite identifiable causal links between administrative decisions and environmental harm. This condition warrants a shift toward a more substantive interpretation of state responsibility to ensure accountability for environmental disasters across Sumatra.